Dimensional variation and evolution of mechanical properties of wet aged composites reinforced with flax fibers. (April 2021) - Hachem, Ziad El; Célino, Amandine; Challita, Georges; Branchu, Samuel; Duigou, Antoine Le; Fréour, Sylvain
The aim of this study is to investigate the dimensional variation of polypropylene composites reinforced with UD flax fibers, and the modification of its dynamical mechanical properties after moisture absorption. The effects of fiber content, coupling agent and moisture content were also examined. Results have shown that the swelling increases significantly when increasing the fiber content and the moisture content. It was also concluded that the addition of a coupling agent reduces the swelling of the composite, by improving the adhesion at the fiber/matrix interface. It is interesting to note that the coefficient of hygroscopic swelling of the composites presents a non-linear evolution, with respect to moisture content. Moreover, it was proved that the addition of fiber and the presence of a coupling agent improve the dynamical mechanical properties of the material. However, following moisture absorption, the storage modulus seems to be decreasing, which might be due to the micro-cracks created as a result of the internal swelling of fibers. Additionally, the coupling agent was found to increase the storage modulus of the composite at dry state, whereas following moisture absorption, it was found that the coupling agent does not modify the storage modulus of the material. Moreover, the results reveal that the dynamic mechanical properties of the composites are hardly dependent on the quality of the material, such as the state of the adhesion at the fiber/matrix interface, a possible misalignment of the fibers within the material and the moisture content within the material at the testing time.